La experiencia de la imaginación creadora como elemento primordial de la creación poética en la infancia. (2009)
The connection between perception, thought processes and creation is an aesthetic experience that comes from creative imagination, a central faculty of the human mind. This connection develops since childhood. This article contains a brief review of the main theoretical approaches to the concept of imagination. I argue that the process of imagination in early childhood, as seen by Gaston Bachelard, is a poetic experience that can lead to poetic creation.